The various rising tones in Newcastle English: a phonological distinction? - Sophie Herment; Laetitia Leonarduzzi; Caroline Bouzon (Anglophonia)
It is acknowledged in the literature that Newcastle English is characterised by the use of rising tones as the default tone, Tyneside English being part as such of those varieties displaying a typical Urban Northern British Intonation (UNBI). A previous study on Newcastle English performed on the NECTE corpus allowed to make out two main types of rises: simple rises or rise-plateaus on the one hand, and up-stepped level tones on the other hand. In this study we hypothesise that the difference between these two types of rises is a phonological rather than a phonetic distinction, meaning that each type of rise has a specific function. We tested this hypothesis by carrying out a pilot study based on a perception experiment. The test fails to show a clear phonological difference between the two types of rises but confirms that Newcastle English belongs to the UNBI group. The results of the test lead us towards another hypothesis, namely that one of our rising contours would actually be a contour known as HRT (High Rising Terminal or Uptalk). HRT has indeed begun to spread through UNBI varieties, and this would be the case in Newcastle, where there would be a coexistence between the two intonations. If this were to be the case, then it could be said that there is a phonological distinction between the two types of rises since it has been demonstrated that HRTs have interactional functions.